Restraint Stress-Induced Morphological Changes at the Blood-Brain Barrier in Adult Rats - Sántha, Petra; Veszelka, Szilvia; Hoyk, Zsófia; Mészáros, Mária; Walter, Fruzsina R.; Tóth, Andrea E.; Kiss, Lóránd; Kincses, András; Oláh, Zita; Seprényi, György; Rákhely, Gábor; Dér, András; et al. (Frontiers in Molecular Neuroscience, 2016)
Stress is well known to contribute to the development of both neurological and psychiatric diseases. While the role of the blood-brain barrier is increasingly recognised in the development of neurodegenerative disorders, such as Alzheimer’s disease, dysfunction of the blood-brain barrier has been linked to stress-related psychiatric diseases only recently. In the present study the effects of restraint stress with different duration (1, 3 and 21 days) were investigated on the morphology of the blood-brain barrier in male adult Wistar rats. Frontal cortex and hippocampus sections were immunostained for markers of brain endothelial cells (claudin-5, occludin and glucose transporter-1) and astroglia (GFAP). Staining pattern and intensity were visualized by confocal microscopy and evaluated by several types of image analysis. The ultrastructure of brain capillaries was investigated by electron microscopy. Morphological changes and intensity alterations in brain endothelial tight junction proteins claudin-5 and occludin were induced by stress. Following restraint stress significant increases in the fluorescence intensity of glucose transporter-1 were detected in brain endothelial cells in the frontal cortex and hippocampus. Significant reductions in GFAP fluorescence intensity were observed in the frontal cortex in all stress groups. As observed by electron microscopy, one-day acute stress induced morphological changes indicating damage in capillary endothelial cells in both brain regions. After 21 days of stress thicker and irregular capillary basal membranes in the hippocampus and edema in astrocytes in both regions were seen. These findings indicate that stress exerts time-dependent changes in the staining pattern of tight junction proteins occludin, claudin-5 and glucose transporter-1 at the level of brain capillaries and in the ultrastructure of brain endothelial cells and astroglial endfeet, which may contribute to neurodegenerative processes, cognitive and behavioral dysfunctions.